Phenology of woody species: a review - González Rodríguez, Humberto; Maiti, Ratikanta; Sarkar, N. C. (Pushpa Publishing House, 2014)
An attempt has been made to synthesize a brief account on research advances on various phases of phenology. Climate has positive impact on the timing of phenology; cold-air drainage may influence the start of leaf growth, however leaf phenology in tropical evergreen forests is not determined by the seasonality of precipitation. Climate warming in late winter and spring may enhance sensitivity of the growing season’s spatial response due to the relationship of beginning date to temperature. Elevated temperature strongly influences greater in C3 plants than in C4 plants but the disadvantages of warming may be considerably attenuated by elevated CO2, especially for C3 grasses. Species with high wood densities can able to store only limited quantities of water in their trunks; leaf fall in these species occurred during the dry season. Flowering phenology may be changing faster and precipitation may play a more important role in semi-arid grasslands than in humid-temperate systems. Peak flowering and fruiting are dependent on seasons for both endemic and non-endemic species. Population sensitivity to global warming might be stable for a given species, in spite of its possible local adaptation. It might be possible for ecologists to establish comprehensive networks for long-term monitoring of potential photosynthetic capacity from regional to global scales by linking satellite-based programme. Use of satellite-derived metrics,such as VARI, may be used for evaluating the spatial patterns and temporal dynamics of species composition across broad geographic regions.